Rumination and Identity Confusion as Predictors of Emotional Exhaustion in Emerging Adult Women - Rahman, Farhana; Al-Taie, Zainab (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the predictive roles of rumination and identity confusion in emotional exhaustion among emerging adult women.Methods and Materials: A correlational descriptive design was employed with a sample of 392 emerging adult women in Iraq, selected based on Morgan and Krejcie’s sample size table. Participants completed standardized self-report instruments measuring emotional exhaustion, rumination, and identity confusion. Descriptive statistics, Pearson correlation coefficients, and multiple linear regression analyses were conducted using SPSS version 27. All assumptions for regression, including normality, linearity, homoscedasticity, multicollinearity, and independence of residuals, were checked and confirmed prior to analysis.Findings: The results revealed significant and positive correlations between emotional exhaustion and both rumination (r = .56, p < .001) and identity confusion (r = .48, p < .001). Multiple linear regression analysis indicated that rumination (B = 0.24, β = .46, t = 8.63, p < .001) and identity confusion (B = 0.19, β = .31, t = 6.02, p < .001) significantly predicted emotional exhaustion. The overall regression model was statistically significant, F(2, 389) = 127.36, p < .001, accounting for 40% of the variance in emotional exhaustion (R² = .40, adjusted R² = .39).Conclusion: This study provides empirical evidence that rumination and identity confusion are significant cognitive and developmental predictors of emotional exhaustion in emerging adult women. The findings highlight the importance of addressing maladaptive thought patterns and unresolved identity issues during this life stage to mitigate psychological fatigue and promote emotional well-being. Interventions targeting cognitive restructuring and identity coherence may be effective in reducing the risk of emotional exhaustion in this vulnerable population.